An evaluation of the effectiveness of interactive multimedia to enhance divergent analytical thinking skills - Mohd. Sukor, Hamizer (2006)
The purpose of this research is to develop and evaluate the effectiveness of an interactive multimedia package, based on students’ design preferences in non-academic domain content with an aim of enhancing students’ divergent analytical thinking skills in a collaborative learning environment. This study defines divergent analytical thinking as consisting of identifying and analyzing statements by considering different viewpoints. The modus operandi of the package is the sharing of text files in an asynchronous mode in which students’ responses can be publicly accessed and judged by their peers. It utilized the IT infrastructure already set up in smart schools. A quasi-experimental research design of nonrandomized control group, pre-test-post-test design was used. The research samples consisted of 233 students in experimental and 81 students in control groups consisting of Form Four students in three fully residential smart schools in Johore. The students were divided into three groups, each working on one specific module only. Data were gathered using pre-test and post-test responses, observations and group interviews. ANOVA testing indicated that the package significantly enhanced the experimental groups’ performance compared to the control group for all the three modules (significant level a = 0.05). No correlation with gender was found for all the three modules. The study indicated a positive correlation between levels of personal satisfactions on features of the package design to the extent of initial enhancements in performance score after first exposure to the package with respect to pre-test score. After a second exposure to the package, the disparity began to disappear for some students. The study also uncovered positive attitudinal transformation amongst the students in the experimental group